Validation of the novel transdermal arterial gasotransmitter sensor (TAGS™) system in measuring transdermal hydrogen sulfide in human subjects - Matheson, B.T.; Osofsky, R.B.; Friedrichsen, D.M.; Brooks, B.J.; Clark, R.M.; Kanagy, N.L.; Shekarriz, R. (Sensing and Bio-Sensing Research, 2022)
A novel non-invasive system has been developed to measure transdermally emitted hydrogen sulfide (H2S) from the upper and lower limbs of human subjects. The transdermal arterial gasotransmitter sensor (TAGS™) has previously been shown to detect low levels of H2S ranging between 1 and 100 ppb considered relevant for physiological measurements (Shekarriz et al. 2020). This study was designed to compare its measurement precision in detecting transdermal H2S to a commercially available chemiluminescent device, the H2S-selective Ecotech Serinus 55 TRS™. Although TAGS™ does in-situ and real-time sampling, the comparative studies in this paper collected gases emitted from the lower arm of 10 heathy human subjects between the ages of 30 and 60. Three replicate samples of each individual were collected for 30 min in a sealed 10 L Tedlar® bag to allow readings from the same sample by both devices. Readings from the TAGS™ system correlated strongly with the values obtained from the Serinus™ device, both ranging between 0.31 ppb/min and 2.21 ppb/min, with a correlation coefficient of R2 = 0.8691, p < 0.0001. These results indicate that TAGS™ measures transdermal H2S specifically and accurately. Because vascular endothelial cells are a known source of H2S, TAGS™ measurements may provide a non-invasive means of detecting endothelial dysfunction, the underlying cause of peripheral artery disease (PAD) and microvascular disease. TAGS™ has potential clinical applications such as monitoring skin vascular perfusion in individuals with suspected vascular disease or to monitor progression of wound healing during treatment, which is of particular value in diabetic patients with calcified arteries limiting detection options.